1977
DOI: 10.1038/bjc.1977.147
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes and macrophages in malignant melanoma. I. Peripheral blood macrophage precursors

Abstract: A micro-assay designed to assess the capacity of peripheral blood mononuclear cells to differentiate in vitro into mature macrophages is described. In patients with "final common pathway" malignant melanoma, there was a highly significant deficiency in macrophage precursors (MPs). By conventional morphological criteria such patients did not show a significant monocytopenia. Serum factors do not seem to contribute to the MP defect in the patients. We conclude that these patients have an intrinsic functional def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 11 publications
4
19
0
Order By: Relevance
“…Monocyte maturation.-This was based on the assay described by Currie & Hedley (1977). Blood was drawn between 08:30 and 11:00 and the sample divided into 2.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocyte maturation.-This was based on the assay described by Currie & Hedley (1977). Blood was drawn between 08:30 and 11:00 and the sample divided into 2.…”
Section: Patientsmentioning
confidence: 99%
“…Metabolic activity (King et al, 1977), in vivo phagocytic capacity (Margarey & Baum, 1977) and Fc-receptor expression (Rhodes,1 977b) are increased but, conversely, migration in vivo (Dizon & Southam, 1963) and in vitro (Snyderman et al, 1977) is decreased. Monocyte production from marrow in animals is increased (Meuret et al, 1977) but recent reports suggest that the ability of monocytes to mature into macrophages in vitro is reduced (Currie & Hedley, 1977;Taylor & Currie, 1979). This lack of ability to mature has been shown to be related to prognosis in primary breast cancer (Taylor & Currie, 1979) and to be restored by treatment with Corynebacteriurn parvurn in patients with malignant melanoma (Hedley et al, 1979).…”
mentioning
confidence: 99%
“…The findings with local macrophages were rather disappointing, considering the experimental literature with animal tumours (Evans, 1 972;Eccles & Alexander, 1974) and the vast number of in vitro studies on macrophage and tumour-cell interactions (Keller, 1976). The unreliability of these cells as prognostic indicators could result from their functional insufficiency in animal and human tumour bearers (Normann & Sorkin, 1976;McVie et al, 1977;Currie & Hedley, 1977;Normann et al, 1979). It would appear from our observations that macrophages indicate a favourable prognosis at early stages if they occur together with eosinophils, in the context (as we believe) of an immune reaction.…”
Section: R Nr R Nr R Nr R Nr R Nr R Nr R Nrr Nr R Nr R Nr R Nr R Nrmentioning
confidence: 99%
“…Monocyte maturation.-In brief, this method examines the ability of monocytes to mature into macrophages when cultured in 500°fresh autologous serum at 37°C for 7 days in the wells of 3040 (Falcon Plastics) microplates (Currie & Hedley, 1977 (Hedley & Currie, 1978). The rate of dye reduction is an indirect measure of hexose-monophosphate-shunt activity, the enhancement of which is associated with monocyte "activation".…”
Section: Assays Of Monocyte Functionmentioning
confidence: 99%
“…Monocyte function in patients with malignant melanoma is disturbed. Using assays designed to examine 3 different aspects of monocyte function (differentiation, NBT reduction and lysis of opsonized erythrocytes) we have previously obtained evidence (Currie & Hedley, 1977;Hedley & Currie, 1978) that the detectable abnormalities may be related to clinical tumour burden. In brief, these earlier studies showed that, in patients with minimal tumour burden, peripheral blood monocytes, although showing defective differentiation, are "activated" relative to agematched control donors, and that these monocyte functions become depressed in patients with overt disseminated disease.…”
mentioning
confidence: 99%